Neuroprotective antioxidant-based therapeutic properties of Malaysian medicinal plants in Javanese medaka (Oryzias javanicus Bleeker, 1854) - Ibrahim, Hassan Maina (2017)
Accumulation of heavy metals such as arsenic has been identified as an endogenous neurotoxin that caused stroke, Alzheimer’s disease (AD) and Parkinson disease (PD). Current treatments for those neurodegenerative diseases are not effective and caused many side effects. Thus, the search for alternative medicines is in high demand. Therefore, the aim of this study is to evaluate the antioxidant and neuroprotective properties of Malaysian medicinal plants using in vitro and in vivo models. Initially, 10 plant extracts, which were Melastoma malabathricum (leaf and stem), Polygonum minus (leaf and stem), Ficus deltoidea (leaf), Phaleria macrocarpa (leaf), Clinacanthus nutans (leaf), Murraya koenigii (leaf), Curcuma longa (leaf), Paederia foetida (leaf) including the reference plants extracts which were Curcuma longa (rhizome) and Ginkgo biloba (seed) were extracted using 80% methanol and screened for antioxidant activities using DPPH and FRAP assays as well as in vitro and in vivo toxicity effects on human neuroblastoma cells line (SH-SY5Y) and zebrafish (Danio rerio) embryos, respectively. Screening results showed that Melastoma malabathricum (leaf and stem), Murraya koenigii (leaf), Curcuma longa (leaf and rhizome), Ficus deltoidea (leaf), Phaleria macrocarpa (leaf) and Ginkgo biloba (seed) demonstrated high antioxidant activities with IC50 range of 1–100 μg/mL in both DPPH and FRAP assays. Among the active plants, Curcuma longa (leaf) and Ginkgo biloba (seed) showed no toxicity effects with LC50 values >1000 μg/mL, while Melastoma malabathricum (leaf and stem), Polygonum minus (stem) and Ficus deltoidea (leaf) showed low toxicity effects on SH-SY5Y cells with 50% lethal concentration (LC50) range 500-1000 μg/mL. On the other hand, Paederia foetida (leaf), Curcuma longa (leaf) and Ginkgo biloba (seed) showed low toxicity effects towards zebrafish embryos with LC50 range 500-1000 μg/mL. However, Polygonum minus (leaf) and Curcuma longa (rhizome) showed high toxicity effects on SH-SY5Y cells with lethal concentration (LC50) range of 199.7±0.46 and 185.7±0.21 μg/mL, repectively. While, Clinacanthus nutans (leaf) and Curcuma longa (rhizome) showed high toxicity effects towards zebrafish embryo with LC50 80.6±0.64 and 51.4±0.6 μg/mL, respectively. Based on antioxidant and toxicity screening, two plant extracts which were Ficus deltoidea (leaf) and Phaleria macrocarpa (leaf) were selected for in vitro and in vivo neuroprotectvie evaluation in SH-SY5Y cells and adult Javanese medaka (Oryzias javanicus). Antioxidant using dichlorofuoresence diacetate (DCF-DA) assay on SH-SY5Y cells revealed high activities of Ficus deltoidea (leaf) and Phaleria macrocarpa (leaf) at IC50 of 177.78±0.8 μg/mL and 146.66±0.1 μg/mL, respectively. Subacute and chronic toxicity tests of selected plant extracts at concentration of 0-95 mg/L were conducted on adult Javanese medaka (Oryzias javanicus). Results showed that Ficus deltoidea (leaf) and Phaleria macrocarpa (leaf) demonstrated no toxicity effect on subacute and chronic toxicity tests in adult Javanese medaka (Oryzias javanicus) with LC50 >1000 μg/mL. Neuroprotective test using acetyl-cholinesterase, butyryl- cholinesterase and propionyl-cholinesterase assays disclose significant differences at P<0.05 between the treated and non treated groups by both selected plants. Phytochemical analyses showed that vitexin, isovitexin, glycine, methylamine and dimethylamine were bioactive compounds in Ficus deltoidea (leaf) while mahkoside A (4, 4′ dihydroxy-2-methoxybenzophenone-6-O-β-D-glucopyranoside) was bioactive compound in Phaleria macrocarpa (leaf), which might contributed to their high antioxidant and neuroprotective effects. This study has revealed the antioxidant and neuroprotective potential of Ficus deltoidea (leaf) and Phaleria macrocarpa (leaf). Thus, both plants could be developed as new anti-oxidant based neuroprotective supplement/ herbal products to treat neurodegenerative diseases.